An Incentive Mechanism for Cooperative Data Replication in MANETs - A Game Theoretical Approach - Alireza Tajalli; Seyed-Amin Hosseini-Seno; Mohamed Shenify; Rahmat Budiarto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Wireless ad hoc networks have seen a great deal of attention in the past years, especially in cases where no infrastructure is available. The main goal in these networks is to provide good data accessibility for participants. Because of the wireless nodes’ continuous movement, network partitioning occurs very often. In order to subside the negative effects of this partitioning and improve data accessibility and reliability, data is replicated in nodes other than the original owner of data. This duplication costs in terms of nodes’ storage space and energy. Hence, autonomous nodes may behave selfishly in this cooperative process and do not replicate data. This kind of phenomenon is referred to as a strategic situation and is best modeled and analyzed using the game theory concept. In order to address this problem we propose a game theory data replication scheme by using the repeated game concept and prove that it is in the nodes’ best interest to cooperate fully in the replication process if our mechanism is used.